2019
DOI: 10.1089/mdr.2018.0365
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resistance to Carbapenems inProteus mirabilisMediated by Amplification of theblaVIM-1-Carrying and IS26-Associated Class 1 Integron

Abstract: The aim of the study was to decipher the mechanisms and associated genetic determinants responsible for increased carbapenem resistance among Proteus mirabilis clinical isolates. Methods: The entire genetic structure surrounding the b-lactam resistance genes was characterized by PCR, gene walking, and DNA sequencing. Results: A series of clinical P. mirabilis isolates were consecutively recovered from different patients at the Military hospital of Sofia, Bulgaria. They showed variable levels of resistance to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Not detected were aacC3, bla PSE , bla VIM , bla KPC , and bla IMP . In addition, in the recent 25 yr of reports on the drug resistance of P. mirabilis , the most resistant has been the β-lactamase-producing P. mirabilis ( Bontron et al, 2019 ), which is distributed all over the world and has many types, including broad-spectrum β-lactamase ( ESBLs ) ( Sohn et al, 2011 ), cephalosporinase ( AmpC ) ( Jacoby, 2009 ), and carbapenemase, among which ESBLs are mainly the TEM and CTX-M types ( Nakano et al, 2012 ). In this study, the detection rate of β-lactamase resistance genes was as high as 88% (44/50).…”
Section: Discussionmentioning
confidence: 99%
“…Not detected were aacC3, bla PSE , bla VIM , bla KPC , and bla IMP . In addition, in the recent 25 yr of reports on the drug resistance of P. mirabilis , the most resistant has been the β-lactamase-producing P. mirabilis ( Bontron et al, 2019 ), which is distributed all over the world and has many types, including broad-spectrum β-lactamase ( ESBLs ) ( Sohn et al, 2011 ), cephalosporinase ( AmpC ) ( Jacoby, 2009 ), and carbapenemase, among which ESBLs are mainly the TEM and CTX-M types ( Nakano et al, 2012 ). In this study, the detection rate of β-lactamase resistance genes was as high as 88% (44/50).…”
Section: Discussionmentioning
confidence: 99%
“…These strains did not show a gene substrate for OXA-48 synthesis. However, studies have shown that P. mirabilis-CR strains are versatile in terms of carbapenemase production, MBL-NDM, VIMand IMP, 8,[34][35][36] or KPC-producing strains being frequently reported. 6,7,9 With regards to the P. rettgeri strain, this was confirmed to be MBL-NDM type.…”
Section: Discussionmentioning
confidence: 99%
“…These genes may be carried on genetic elements such as plasmids, transposons and on integrons that can be mobilized [12]. Previously, the emergence of multidrug-resistant P. mirabilis-producing extended spectrum beta lactamase, AmpC, and carbapenemases has been reported [19,20]. Since there is a trend of developing resistance to various antimicrobial drugs, it is important to investigate new drugs, combination therapies or methods to overcome antimicrobial resistance problems caused by P. mirabilis bacteria.…”
Section: Introductionmentioning
confidence: 99%